Effect of crumb rubber concentration on the physical and rheological properties of rubberised bitumen binders - Mashaan, N.S.; Ali, A.H.; Karim, Mohamed Rehan; Abdelaziz, M. (Academic Journals, 2011)
The increase use of crumb rubber in flexible pavements requires the better understanding of its effect on physical and rheological properties of rubberised bitumen binders. The performance properties of rubberised bitumen binder are influenced by the blending conditions and crumb rubber content. The main objective of this research is to investigate the effect of various crumb rubber content on the physical, rheological properties and rutting resistance of rubberised bitumen. Laboratory tests were conducted to evaluate such related properties of bitumen binder with different rubber contents. The tests undertaken comprise the ductility test, elastic recovery test, penetration test and dynamic shear rheometer (DSR) test. The results showed that the addition of crumb rubber has an effect on the physical properties of rubberised bitumen binders, by increasing its elastic recovery and decreasing its penetration and ductility. The rubberised bitumen binder with higher crumb rubber content has an obvious effect on the rheological properties (increase in complex shear modulus G, storage modulus G', loss modulus G'' and decrease in phase angle Î´). The results indicated that the rubber content has the potential to resist rutting deformation that occurs in road pavement as result of increased traffic loading.